PERBANDINGAN PENGGUNAAN FACE OIL DAN MOISTURIZER TERHADAP HASIL MAKEUP PENGANTIN INTERNASIONAL PADA JENIS KULIT WAJAH KOMBINASI - Adinda Yulia Sari; Dindy Sinta Megasari; Octaverina Kecvara Pritasari; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2025)
Perfect makeup results are the main focus of this research, especially in international bridal makeup, so choosing the right cosmetics is very important, especially for combination facial skin, so that the makeup sticks perfectly and lasts long. This study aims to determine: 1) the effect of using face oil on international bridal makeup on combination facial skin, 2) the effect of using moisturizer on international bridal makeup on combination facial skin, and 3) the difference in the results of international bridal makeup using face oil and moisturizer on combination facial skin. The research method used was experimental, with face oil and moisturizer as independent variables, and makeup results as the dependent variable. The results showed that the use of face oil produced an average of 3.52, classified as very good, while the use of moisturizer produced an average of 3.11, classified as good. The t-test showed a calculated t value of 3.647 with 58 degrees of freedom and a significant value of 0.001. Because 0.001 < 0.05, it can be concluded that in this study there is a significant difference between the use of face oil and moisturizer on the results of international bridal makeup on combination facial skin. With the final result, face oil scored higher than moisturizer. Keywords: face oil, moisturizer, international bridal makeup, combination skin